Effect of Height of Harvesting and Intercropping with Lemongrass [Cymbopogon Flexuosus (Nees Ex. Steud) Wats.] on Biomass and Essential Oil Yields of Lemon Scented Gum (Eucalyptus Citriodora Hook) - Chand, Sukhmal; Rajeswara Rao, B. R.; Kaul, P. N.; Bhattacharya, A. K.; Singh, K.; Singh, C. P. (Indian Forester, 1998)
Two field experiments were conducted during the vegetation periods of 1990-92 under the semiarid tropicai climatic conditions at CIMAP Field Station, Hyderabad, Andhra Pradesh to study the effects of the height of harvesting and inter cropping lemongrass in lemon-scented gum. Lemonscented gum produced highest biomass and essential oil yields, gross and net profits when pollarded at 1.0 m height than when coppiced at 0.15 m height or pollarded at 1.5 m height. Two rows of lemongrass when intercropped in lemon-scented gum produced bonus yield of lemongrass oil without adversely affecting the biomass and essential oil yields of lemon-scented gum. This agroforestry system gave gross and net profit ofRs. 79,933 and Rs. 53,067 per heetare, respectively. Freshly distilled oil was of good quality with 79.7% ei tronellal, 4.7% isoJ1ulegol, 5.4% eitronellol, bu t on storage the oil quality deteriorated with 50.4% citronellal, 14.3% isopulegol and 17.3% eitronellol, therefore the oil should be disposed off quickly.